Are South East Asia Countries Capital Markets Characterized by Nonlinear Structures? An Investigation from Indonesia, Philippine and Singapore Capital Market Indices - Bakara, Minarnita Yanti Verawati; Hermanto, Bambang (The Indonesian Capital Market Review, 2009)
This research paper tries to detect the nonlinear structure in the South East Asia Countries Capital Markets. The capital markets of three South East Asia Countries are chosen: Indonesia, Philippine, and Singapore. Daily return data of Capital Markets composite indices are observed: Straits Times Index (STI) of Singapore Exchange from January 04, 1985 to December 31, 2007, Pilipino Stock Exchange Index (PSEi) of Philippines Stock Exchange from March 1, 1990 to December 31, 2007 and Jakarta Composite Index (JCI) of Indonesia Stock Exchange from January 05, 1988 to December 31, 2007. Should nonlinearity be found, the outcomes of each observation are compared to analyze the implications of each country in global, regional and local position of their competition in the continuously changing world of interdependency environment. The implications of nonlinearity finding in the three ASEAN countries capital markets to the current issues of AFAS on Financial Services, Harmonization among ASEAN countries capital markets in the ASEAN region and ASEAN integration and liberalization on Financial Services are analyzed. BDS statistic and R/S Analysis as our tools for nonlinearity testing are applied. Nonlinearity evidences in Jakarta Composite Index, Pilipino Stock Exchange Index and Straits Times Index are found.